The history of the study of the Russian population of Dagestan and the Terek Cossacks (XVIII – early XXI century): historical and bibliographic review - Abidat A., Gazieva; Ruslan I., Seferbekov; Olga B., Khalidova (Kavkazologiya, 2023)
This paper presents a historiographical review of studies about the history of Russians and Cos-sacks of Dagestan and the North Caucasus in the late Middle Ages, modern, soviet and contempo-rary times. The history of the study of the Russians and the Cossacks in each of these historical periods had its own characteristics and was determined by the socio-political, socio-economic and cultural processes occurring in the country. The authors believe that the most complete and com-prehensive, free from ideological attitudes, historical and ethnographic study of the Russians and the Cossacks, was conducted in modern times. This is because of the new paradigm of the state and social structure of Russia, associated with the unfavorable international political and econom-ic situation, the global challenges of our time; such as an increase in ethnic self-awareness of the Russians who make up most of the population; bring awareness to their responsibility for the peo-ples’ fate of Russia and the entire world. Further study of the historiography of various groups of the domestic and foreign Russian population and the Cossacks is promising to create generalizing works on the history and ethnography of Russians in Russia and other countries of the world. In the article, based on the analysis of the works of the authors of pre-revolutionary, Soviet and modern historiography, using historical-genetic, comparative-historical, typological and his-torical-systemic methods, a historical and bibliographic review of the main works on the history of Russians and the Cossacks of Dagestan and the North Caucasus is given.